Ecosystem functioning of two marine food webs in the North‐Western Ionian Sea (Central Mediterranean Sea). Issue 18 (3rd September 2019) - Ricci, Pasquale; Libralato, Simone; Capezzuto, Francesca; D'Onghia, Gianfranco; Maiorano, Porzia; Sion, Letizia; Tursi, Angelo; Solidoro, Cosimo; Carlucci, Roberto
Abstract: The ecosystem functioning of two marine food webs covering the north‐eastern (Salento) and south‐western (Calabria) sectors of the North‐Western Ionian Sea (NWIS) (Central Mediterranean Sea) was investigated through a food‐web model. Data inputs covered a wide set of ecological information applied to 58 functional groups (FGs). The sum of consumption and the mean predation mortality rate were calculated for benthic, demersal, and pelagic subsystems indicating the predator and prey roles of the FGs. A complex system of energy and biomass exchanges characterized the investigated food webs indicating an important benthic‐pelagic coupling. In the food webs of both areas, the regulation of flows between the benthic‐pelagic coupling seems to occur through the benthopelagic shrimps and the small pelagics due to their wasp‐waist control role. Differences were observed concerning the top predators. Odontocetes play this keystone role in the Salento food web. Anglers, bathyal squids, and sharks assume this functional role in Calabria. The geomorphology and hydrography in the NWIS could affect the biomass and energy exchanges in this coupling. The higher flows of consumption of the benthic system observed in the Calabria food web could be influenced by a widespread presence of canyons along the continental edge which increase the benthic productivity. In contrast, the flows of consumption in the Salento food web seem to be driven by the planktonic productivity supporting the pelagic, benthopelagic, and demersal compartments. This condition could be favored by the large extension of the shelf break zone. The food‐web models realized for the NWIS represent ideal platforms for the development of analysis with dynamic simulations. The comparative analysis of the two food webs by means of the FGs and their functional traits allowed the general pattern of ecosystem structure and functioning in the NWIS to be identified, making it an interesting approach to investigate the marine ecosystem. Abstract : The ecosystem functioning of two marine food webs covering the north‐eastern (Salento) and south‐western (Calabria) sectors of the North‐Western Ionian Sea (NWIS) (Central Mediterranean Sea) was investigated by means of a tropho‐dynamic model. The comparative analysis of the two food webs by means the functional groups and their functional traits allowed the general pattern of ecosystem structure and functioning in NWIS to be identified, making it an interesting approach to investigate the marine ecosystem.